2021
DOI: 10.1111/mam.12242
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the threats facing wetland mammals in India using an evidence‐based conservation approach

Abstract: 1. Environmental change and anthropogenic pressure are primary drivers of biodiversity loss, particularly in wetland ecosystems that have been modified significantly. Among wetland specialists, mammals may be particularly vulnerable to extinction. We aimed to increase understanding of threats and knowledge gaps faced by 11 mammal species inhabiting wetlands throughout India. 2. We adopted a systematic literature search protocol following an evidencebased conservation approach to obtain information on conservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…However, it is very important to understand that despite government efforts, debates and citizen participation, urban wetlands are ecosystems that are extreme fragile and particularly vulnerable to urban changes and anthropogenic pressure, as was mentioned by Chatterjee and Bhattacharyya (2021) [43] (2021). The authors note that severe habitat fragmentations are primary drivers of biodiversity loss, and that mammals are particularly vulnerable to this fragmentation.…”
Section: Background and Related Workmentioning
confidence: 99%
“…However, it is very important to understand that despite government efforts, debates and citizen participation, urban wetlands are ecosystems that are extreme fragile and particularly vulnerable to urban changes and anthropogenic pressure, as was mentioned by Chatterjee and Bhattacharyya (2021) [43] (2021). The authors note that severe habitat fragmentations are primary drivers of biodiversity loss, and that mammals are particularly vulnerable to this fragmentation.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Wetlands also host exceptionally high levels of biodiversity, which is attributed to their high spatial and temporal environmental heterogeneity (Keddy et al, 2009). Wetlands are home to numerous organisms including phytoplankton and zooplankton species (hereafter: plankton) (D' Ambrosio et al, 2016;Gogoi et al, 2019), macroinvertebrates (Mereta et al, 2013;Gezie et al, 2019), aquatic plants (Getnet et al, 2021), fish (Aziz et al, 2021), amphibians (Nagel et al, 2021), waterbirds (Aynalem and Bekele, 2008;Chawaka et al, 2018a;Chawaka et al, 2018b), and mammals (Chatterjee and Bhattacharyya, 2021). Phytoplankton form the base of the food chain in aquatic ecosystems and play an important role in overall wetland productivity (Chengxue et al, 2019), while zooplankton are recognized as the main primary consumers.…”
Section: Introductionmentioning
confidence: 99%
“…In India, there have been frequent general discussions about dam effects on biodiversity, but detailed empirical studies on the dynamics and distribution of forest mammals within riparian forests remain virtually non-existent. In regards to riparian forests, studies have mainly focused on riparian obligate species like otters (Umapathy and Durairaj, 1995;Hussain and Choudhury, 1997;Anoop and Hussain, 2006a,b;Perinchery et al, 2011;Prakash et al, 2012;Raha and Hussain, 2016), or certain large mammals in floodplains/wetland-dependent species, such as Asiatic buffalo and rhinocerous (Chatterjee and Bhattacharyya, 2021). Chatterjee and Bhattacharyya (2021) found that even though wetland-dependent mammals have been studied, there remains a large knowledge gap in regards to these species ecology and conservation.…”
Section: Introductionmentioning
confidence: 99%